Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada CV Kusuma Putra Di Kota Batam - Kasidi, Daniel (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2023)
The purpose of this research was to know the influences of service quality and price on customer satisfaction atCV Kusuma Putra in Batam City. This research also aims to analyse the most dominant factors that influence to customer satisfaction. Hypothesis are service quality and price have positive influence towards customers satisfaction. The population of this research are 50 customers.This study did not use certain sampling techniques because population numbers are limited, therefore all members of the population are used as samples. The methods used in this research is quantitative methods through survey approach. The data are collected by the questionnaire until the Likert scale. The results of research show that the independent variable service quality does not affect on customer satisfaction, free variable rates have an impact on customer satisfaction and promotion does not affect the customers satisfaction. By using F test know that collectively the quality of service, price and promotion has impact on customer satisfaction. Figure R2 of 0.389 or 38.9% variation shows that customer satisfaction can be explained by a third variable in the regression equation. While the rest of 61.1% explained by other variables which not included in this research.